Answer:
-3x2 + 12x - 8
Step-by-step explanation:
Equation at the end of step 1
((0 - 3x2) + 12x) - 8
STEP
2
:
STEP
3
:
Pulling out like terms
3.1 Pull out like factors :
-3x2 + 12x - 8 = -1 • (3x2 - 12x + 8)
Trying to factor by splitting the middle term
3.2 Factoring 3x2 - 12x + 8
The first term is, 3x2 its coefficient is 3 .
The middle term is, -12x its coefficient is -12 .
The last term, "the constant", is +8
Step-1 : Multiply the coefficient of the first term by the constant 3 • 8 = 24
Step-2 : Find two factors of 24 whose sum equals the coefficient of the middle term, which is -12 .
-24 + -1 = -25
-12 + -2 = -14
-8 + -3 = -11
-6 + -4 = -10
-4 + -6 = -10
-3 + -8 = -11
-2 + -12 = -14
-1 + -24 = -25
1 + 24 = 25
2 + 12 = 14
3 + 8 = 11
4 + 6 = 10
6 + 4 = 10
8 + 3 = 11
12 + 2 = 14
24 + 1 = 25
The distributive property is being used because a is being distributed to b and c, which leaves you with ab + ac
1. 13/4
2.60
3. in 36 mins (I don't know about this one)
4.<
5. 3/8< 2/3< 19/24
Answer:
16,30.34
Step-by-step explanation: